Whole-genome sequencing of Schistosoma mansoni reveals extensive diversity with limited selection despite mass drug administration - Duncan J. Berger (Nature Portfolio, 2021)
Schistosomiasis control strategies rely on mass drug administration (MDA) using praziquantel. Here, Berger et al. perform whole-genome sequencing of larvae from infected children across Ugandan regions with differing MDA histories. They find extensive gene flow with limited positive selection suggesting minimal change post MDA.